Open data: Visual load does not decrease the auditory steady state response to 40-Hz amplitude-modulated tones - Stefan Wiens; Malina Szychowska (Stockholm University, 2018)
Open data: Visual load does not decrease the auditory steady state response to 40-Hz amplitude-modulated tones
The main results files are saved separately:
- ASSR_study1.html: R output of the main analyses- ASSR_study1_subset_subjects.html: R output of the main analyses- ASSR_study2.html: R output of the main analyses
The studies were preregistered:Study 1: https://doi.org/10.17605/OSF.IO/UYJVAStudy 2: https://doi.org/10.17605/OSF.IO/JVMFD
DATA & FILE OVERVIEW
File List:The files contain the raw data, scripts, and results of main and supplementary analyses of two electroencephalography (EEG) studies (Study1, Study2). Links to the hardware and software are provided under methodological information.
ASSR_study1_experiment_scripts.zip: contains the Python files to run the experiment.
ASSR_study1_rawdata.zip: contains raw datafiles for each subject
- data_EEG: EEG data in bdf format (generated by Biosemi)- data_log: logfiles of the EEG session (generated by Python)- data_WMC: logfiles of the working memory capacity task (generated by Python)
ASSR_study1_EEG_scripts.zip: Python-MNE scripts to process the EEG data
ASSR_study1_EEG_preprocessed.zip: Preprocessed EEG data from Python-MNE
ASSR_study1_analysis_scripts.zip: R scripts to analyze the data together with the main datafiles. The main files in the folder are:
- ASSR_study1.html: R output of the main analyses- ASSR_study1_subset_subjects.html: R output of the main analyses but after excluding five subjects who were excluded because of stricter, preregistered artifact rejection criteria
ASSR_study1_figures.zip: contains all figures and tables that are created by Python-MNE and R.
ASSR_study2_experiment_scripts.zip: contains the Python files to run the experiment
ASSR_study2_rawdata.zip: contains raw datafiles for each subject
- data_EEG: EEG data in bdf format (generated by Biosemi)- data_log: logfiles of the EEG session (generated by Python)- data_WMC: logfiles of the working memory capacity task (generated by Python)
ASSR_study2_EEG_scripts.zip: Python-MNE scripts to process the EEG data
ASSR_study2_EEG_preprocessed.zip: Preprocessed EEG data from Python-MNE
ASSR_study2_analysis_scripts.zip: R scripts to analyze the data together with the main datafiles. The main files in the folder are:
- ASSR_study2.html: R output of the main analyses- ASSR_compare_performance_between_studies.html: R output of analyses that compare behavioral performance between study 1 and study 2.
ASSR_study2_figures.zip: contains all figures and tables that are created by Python-MNE and R.
Instrument- or software-specific information needed to interpret the data:MNE-Python (Gramfort A., et al., 2013): https://mne.tools/stable/index.html#Rstudio used with R (R Core Team, 2016): https://rstudio.com/products/rstudio/Wiens, S. (2017). Aladins Bayes Factor in R (Version 3). https://www.doi.org/10.17045/sthlmuni.4981154.v3
Keywords: 170101 Biological Psychology (Neuropsychology, Psychopharmacology, Physiological Psychology); Neuroscience and Physiological Psychology; 170112 Sensory Processes, Perception and Performance; Neurosciences; Neurovetenskaper; Biological Sciences; Biologi